La metodología en el proceso de enseñanza aprendizaje de la lectoescritura. - Cárate Ronquillo, Katty de las Mercedes (2020)
This research has been planned, structured and developed with the purpose of contributing to the solution of the research problem that refers how to improve the methodology applied in the teaching learning process of reading and writing in students of second year of Basic Education at the "Dr. José María Velasco Ibarra" Educational Unit In order to develop this study, the general objective was to establish the need to do a methodological proposal for teaching reading and writing to children of second year of Basic Education; methodologically, the process is focused in the qualitative approach, because it seeks to improve the quality of learning; In addition, the inductive method was used, because it allows to relate the theoretical bases with the data obtained , it constitutes an important support in the analysis and interpretation of results; the technique that was used to the research requirements was the interview and the pedagogical test with its instrument the questionnaire; as general conclusions it is pointed out that the structured proposal has been subjected to a process of validation by users, who have placed it in an excellent level. These results allowed to consider that the methodological proposal strengthen the teaching learning process of reading and writing in children of second year of Basic Education of the Educational Unit.